THE EFFECT OF SCIENCE LEARNING MODEL, ENVIRONMENT, TECHNOLOGY, AND SOCIETY ASSISTED BY ENVIRONMENTAL MEDIA ON SCIENCE KNOWLEDGE COMPETENCE OF GRADE V ELEMENTARY SCHOOL STUDENTS OF SRIKANDI CLUSTER EAST DENPASAR IN ACADEMIC YEAR 2017/2018 - Arista dewi, Putu Suwi; Jampel, I N; Jayanta, I N L (Journal of Psychology and Instructions, 2018)
This study aims to determine the effect of Science Learning Model, Environment, Technology, Society assisted Environmental media on Science Competence of grade V students. The type of this research was quasi experiment with non-equivalent group design. The population in this study was the entire class V in the Srikandi cluster East Denpasar amounted to 362 students. The sample of this research was class V of SDN 5 Sumerta were 28 students as experimental group and class V of SDN 10 Sumerta were 28 students as control group. Data collected with multiple choice test instruments, then was analyzed using descriptive statistical analysis and inferential statistical analysis (t-test). Based on the data analysis, tcount = 2.500 and ttabel (5% significance level) = 2,000. This means that tcount = 2,500> ttabel = 2,000. There was a significant difference of science competence between groups of students who was taught by science learning model, Environment, Technology, Society assisted Environmental media and group of students which is learn through conventional learning. The average value of science competence of the experimental group ( ) is 79.00 while the mean score of control group students ( ) is 74.07. This means =79,00 > =74,07, so it can be concluded that the application of learning model of Science, Environment, Technology, Society assisted Environmental media influenced the competence of science. Based on the results of this study it is suggested that the results of this study can be used as a relevant study, especially as supporting the next research.